Eficacia y eficiencia de las decisiones en entornos sistémicos complejos - Acevedo Borrego, Adolfo (2013)
The study identifies the definition of problem situation and how it faces its solution depends on the role of the decision maker, that defines the situation as a problem to solve or demonstrate problems (business case or case of inquiry or investigation), it sequence which facilitates raising and how to solve the problem, considering the efficacy and efficiency of choice. During the stage of hypothesis testing, case studies are considered as working paper, their analyzes let corroborate the hypothesis of research, which shows that the perspective of situation influences analysis and search of solution, and it is corroborated that decision maker’s position and role inside the field of action that covers problematic situation, is relevant to the best choice.